2016
DOI: 10.1038/eye.2016.21
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and severity of upper eyelid skin contracture in facial nerve palsy

Abstract: Purpose To describe the occurrence and severity of upper eyelid skin contracture in facial nerve palsy (FNP). Methods We enroled consecutive patients with unilateral FNP into this study. Patients with previous upper eyelid surgery for either side were excluded. We developed a standardised technique to measure the distance between the upper eyelid margin and the lower border of brow (LMBD). FNP was graded using the Sunnybrook grading scale. Its aetiology, duration, and treatment were noted. Upper and lower marg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 12 publications
1
20
0
Order By: Relevance
“…Based on this theory, they have demonstrated a moderate to significant improvement in lagophthalmos in patients with FNP with manual stretching of the upper eyelid. It has been demonstrated that upper eyelid skin contracture is a frequently observed feature in patients with FNP and contributes to some degree in lagophthalmos 11. FTSGs can support contracted periocular skin and increase its surface area to improve lid position in patients with FNP.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on this theory, they have demonstrated a moderate to significant improvement in lagophthalmos in patients with FNP with manual stretching of the upper eyelid. It has been demonstrated that upper eyelid skin contracture is a frequently observed feature in patients with FNP and contributes to some degree in lagophthalmos 11. FTSGs can support contracted periocular skin and increase its surface area to improve lid position in patients with FNP.…”
Section: Discussionmentioning
confidence: 99%
“…A useful clinical method to help identify the presence of eyelid skin and middle lamella contraction is to assess the upper eyelid margin to brow distance (LMBD) 11 11. FTSGs provide an ancillary procedure to the current surgical armamentarium for patients with FNP where skin contraction exists.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Occurrence and severity of upper eyelid skin contracture in facial nerve palsy, 1 Ziahosseini et al quantitatively demonstrates a shortening of the upper eyelid by a standardized measurement between the upper eyelid margin and the lower border of brow in 66 patients with facial nerve palsy. They explain these findings, seen in 71% of their patients, with contractions of the upper eyelid skin: local atrophy of muscle, and/or soft tissue could result from disuse or diminished activity caused by the palsy.…”
Section: Sir Occurrence and Severity Of Upper Eyelid Skin Contracturmentioning
confidence: 99%